The singing rock & other brand-new fairy tales - Lachenmeyer, Nathaniel 1969-; Blocker, Simini (New York First Second, 2019)
"A genie just wants a chance to grant a wish to the frog who accidentally let him out of his lamp--meanwhile, the frog just wants to be left alone. A witch is tormented by the cheerful (and awful) singing of a persistent bard, but when she finally snaps and turns him into a rock, he just keeps on singing--somehow the power of terrible music overcomes all magic. A wizard wants a pet. An ogre just wants to make beautiful art. Four original, wry and utterly charming fairy tales comprise this new collection for young readers"--Amazon.
Hop hop wish -- Singing rock -- Sorcerer's new pet -- Ogreish art.
GN520L
107409
Keywords: Fairy tales -- Comic books, strips, etc; Fantasy comic books, strips, etc; Magic -- Comic books, strips, etc; Jinn -- Comic books, strips, etc; Witches -- Comic books, strips, etc; Wizards -- Comic books, strips, etc; Ghouls and ogres -- Comic books, strips, etc; Fairy tales -- Fiction; Fantasy; Cartoons and comics; Fantasy comic books, strips, etc; Graphic novels; Fantasy comics; Graphic novels; Comic books, strips, etc..; Comics (Graphic works)